Description of antennal structures of the parasitoid Mallophora ruficauda (Diptera: Asilidae) and its relationship with resources searching behaviour - Groba, Hernán Federico (2014)
The robber fly Mallophora ruficauda is a parasitoid of white grubs (Coleoptera: Scarabaeidae) inhabiting in Pampas region of Argentina. Females locate host’s habitat and lay eggs away from the host in tall grasses. After hatching, larvae fall to the ground and actively seek hosts. Previous works suggested that female would detect the presence of host’s chemical cues, but sensory organs involved in olfaction are still unknown. However, few studies have looked at dipteran parasitoids sensilla, and no study has been undertaken in Asilidae species. The aim of this work was to determine the presence, density, distribution and morphology of chemosensilla in M. ruficauda antennae using optic and scanning microscope techniques. We found that antennae have 4 segments: scape, pedicel, postpedicel and style. We identified basiconic and trichoid sensilla, small and long bristles, and sensory pits. Basiconic sensilla are multiporous and are widely spread between the small bristles through the postpedicel. Trichoid sensilla are grouped in 6–8 units on latero-ventral margin of postpedicel, have mobile base, striated wall and an apical porous. Small bristles are present in the pedicel and postpedicel, and long bristles are found in groups on scape and pedicel. Three different types of sensory pits were observed, with basiconic sensilla, distributed along external and internal lateral side of the postpedicel. Considering the morphological characteristics of the antennae, and based on the olfaction biomechanics, the structure and distribution of these cuticular structures of the parasitoid antennae would contribute to the odour detection mechanism in adults of M. ruficauda.